Affirmative action and long-run changes in group inequality in India - Hemanshu Kumar; Rohini Somanathan (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2016)
Research on caste-based inequalities in India has generally focused on differences between large categories such as the Scheduled Castes, the Scheduled Tribes, and the remainder of the population. We contribute to the literature on horizontal inequalities in India by looking within these groupings, and studying differences between the individual jatis that comprise these categories. Using census data, we find evidence of persistent inequalities in educational outcomes between the jatis, suggesting that socio-economic hierarchies have proved to be stable throughout the post-Independence period. Indeed, the evidence points to divergence: communities with more education in 1961 also had higher educational attainment in 2001. Also, while numerically larger Scheduled Caste communities witnessed greater improvements in educational levels compared to smaller ones, this was not true for the Scheduled Tribes. This may be the result of their greater political mobilization.
Keywords: I24; J15; Z13; 330; caste; tribe; India; disadvantaged groups; horizontal inequalities; affirmative action; education